Constructing consistent work-life histories: a guide for users of the British Household Panel Survey - David C. Mare (University of Essex, Institute for Social and Economic Research (ISER), 2006)
This paper assembles existing documentation about the data available from the British Household Panel Survey (BHPS) that can be used to create consistent and complete work-life histories for respondents. It discusses some of the practical and conceptual challenges in deriving consistent work histories from the BHPS data, and documents aspects of the data and its manipulation. It brings together summaries of how other researchers have dealt with the challenges. It also serves to document a newly derived dataset of consistent work life histories. The material in this paper should be seen as a complement to the BHPS Work-Life History files available though the UK Data Archive. It provides background information on the many issues that were dealt with in the creation of those files. The current paper is intended to assist users of the BHPS to understand the inevitable tradeoffs involved in deriving consistent work-life histories, and to make a well-informed judgement about strengths and weaknesses of the Data Archive files for any specific form of analysis. It also provides guidance for enthusiastic users who wish to derive their own versions of the files.
Keywords: 330